Dynamics of Demand and Supply: Factors that Influence Modern Markets - Nurfatiha Pasya Salsabilla; Rika Rohim; Lia Astrilina; Fika Wahyuni; Zefriyenni (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Demand and supply are two fundamental concepts in economics that determine market equilibrium. In modern markets, the dynamics of demand and supply are not only influenced by classical factors such as prices of goods and consumer income, but also by external factors such as technological developments, changes in consumption trends, government policies, and global economic conditions. Digitalization and e-commerce have changed people's consumption patterns, allowing for increased demand for technology-based goods and services. In addition, social factors, such as changes in lifestyle and consumer preferences, also influence demand patterns. From the supply side, production innovation, supply chain efficiency, and the availability of raw materials are the main factors that determine the amount of goods offered on the market. Economic instability, such as inflation and recession, also affects people's purchasing power and companies' production strategies. Government intervention, through fiscal and monetary policies, has a significant impact on the stability of demand and supply in a country. By understanding the factors that influence these dynamics, business actors and policy makers can make more informed decisions in responding to market changes. Therefore, a comprehensive analysis of the aspects of demand and supply is very important in ensuring sustainable economic balance in the modern era.